Closed-loop power control algorithms for cellular mobile CDMA systems - Sim, Moh Lim. (2009)
In this thesis, the author carried out a thorough study on the performance of a reverse link DS/CDMA system with various fast closed-loop power control algorithms. The algorithms studied include the Conventional single and multiple step-size, and two newly proposed alternatives, i.e., Adaptive step-size, and Predictive power control algorithms. Major parameters affecting the system performance were identified. The relationships between each of these parameters and system performance were examined. Finally, the optimum values for control variables associated with each power control algorithm were obtained or recommended.